The Corridors exercise: a Michael Chekhov-based approach to discovering, experiencing, and embodying Given Circumstances and character biography. Issue 4 (2nd October 2021) - Polanco, Fabio; Walsh, Lionel
Abstract : Slava Kokorin, 2009 winner of the Stanislavski Prize for 'Best Theatre Pedagogue', worked with the Michael Chekhov technique for more than three decades. One of Kokorin's contributions was the development of a Chekhov-based exercise called 'Corridors'. Corridors is grounded in the principles of psychophysical experience and the actor's imagination. Through the images born from the Corridors exercise the actor physically and psychologically discovers, experiences, and embodies a character's Given Circumstances and biography, as well as the character's Objectives, Super-objective, stakes, and urgency. This renders Corridors more effective and efficient than traditional intellectual work on Given Circumstances and character biography; work that many actors and students of acting find cumbersome and dull. Corridors is dynamic, surprising, and immediate because it is based in active creative research. It is an innovative tool for both actor training and character creation. What follows is the lead author's documentation, reflection, and interpretation of the application, meaning, and value of his first experience with Corridors as an actor/student, interspersed with responses and context from his teacher, the co-author. It documents a previously undocumented exercise by an important theatre pedagogue; an exercise that extends the lineage of Michael Chekhov's impactful work.